Clinical Response to Induction Chemotherapy Predicts Outcome after Combined-Modality Therapy in Inflammatory Breast Cancer. (2nd January 2019) - Loi, Mauro; Dunant, Ariane; Ghith, Sahar; Cascales-Garcia, Almudena Maria; Mazouni, Chafika; Pistilli, Barbara; Mathieu, Marie-Christine; Deutsch, Eric; Arriagada, Rodrigo; Rivera, Sofia
Abstract: Purpose: To assess predictors of outcome in a cohort of Inflammatory Breast Cancer (IBC) patients receiving induction chemotherapy followed by local treatment. Methods: We retrospectively reviewed 95 non-metastatic IBC patient files. Results: Complete clinical response (cCR) was obtained in 15 (16%) patients. Median follow up was 13.4 years (IC95%: 10.4–14.6). Loco-regional control (LC), disease-free survival (DFS), and overall survival (OS) at 5 years were 85%, 41%, and 55%, respectively; cCR was associated with better DFS and OS in multivariate analyses adjusted for age ( p  = 0.02). Conclusions: Clinical response to upfront chemotherapy predicts the outcome of patients affected by IBC.